Comparing the effects of an exposure to a polycyclic aromatic hydrocarbon mixture versus individual polycyclic aromatic hydrocarbons during monocyte to macrophage differentiation: Mixture exposure results in altered immune metrics. Issue 10 (8th February 2021) - Tooker, Brian C.; Quinn, Kevin; Armstrong, Michael; Bauer, Alison K.; Reisdorph, Nichole
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are generated by the incomplete combustion of carbon. Exposures correlate with systemic immune dysfunction and overall immune suppression. Real‐world exposures to PAHs are almost always encountered as mixtures; however, research overwhelmingly centers on isolated exposures to a single PAH, benzo[ a ]pyrene (B[ a ]P). Here, a human monocyte line (U937) was exposed to B[ a ]P, benz[ a ]anthracene (B[ a ]A), or a mixture of six PAHs (6‐MIX) to assess the differential toxicity on monocytes. Further, monocytes were exposed to PAHs with and without CYP1A1 inhibitors during macrophage differentiation to delineate PAH exposure and PAH metabolism‐driven alterations to the immune response. U937 monocytes exposed to B[ a ]P, B[ a ]A, or 6‐MIX had higher levels of cellular health and growth not observed following equimolar exposures to other individual PAHs. PAH exposures during differentiation did not alter monocyte‐derived macrophage (MDM) numbers; however, B[ a ]A and 6‐MIX exposures significantly altered M1/M2 polarization in a CYP1A1‐dependent manner. U937‐MDM adherence was differentially suppressed by all three PAH treatments with 6‐MIX exposed U937‐MDM having significantly more adhesion than U937‐MDM exposed to either individual PAH. Finally, 6‐MIX exposures during differentiation reduced U937‐MDM endocytic function significantly less than B[ a ]A exposed cells. Exposure to a unique PAH mixture during U937‐MDM differentiation resulted in mixture‐specific alterations of pro‐inflammatory markers compared to individual PAH exposures. While subtle, these differences highlight the probability that using a model PAH, B[ a ]P, may not accurately reflect the effects of PAH mixture exposures. Therefore, future studies should include various PAH mixtures that encompass probable real‐world PAH exposures for the endpoints under investigation. Abstract : Although exposures to polycyclic aromatic hydrocarbons (PAHs) are almost always exposures to unique PAH mixtures, research centers on exposure to a single PAH. This study reveals that although human monocytes exposed to individual PAHs or a mixture of PAHs had only minor differences in monocyte health or xenobiotic induced gene expression, if these PAH exposures coincided with monocyte‐to‐macrophage differentiation, mixture‐specific alterations in macrophage adhesion, endocytic function, and macrophage polarization markers were observed when compared to individual PAH exposures.